PEMANFAATAN MINYAK SISA LIMBAH PENGGORENGAN KRECEK MENJADI SABUN DAN LILIN DI IKM PANJI JAYA SEGOROYOSO BANTUL YOGYAKARTA - Widia Susanti; RLM. Satrio Ari Wibowo (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2013)
Cooking oil is one of the basic ingredients needed by the Indonesian community, especially the Small and Medium Enterprises (SMEs) in the field of food. Cooking oil is usually used as a medium for frying food and flavor enhancer. A large number of cooking oil used by SMEs cause high amount of waste which prompts to various diseases. Therefore, this research attempts to use the waste cooking oil in order to prevent from environmental pollution by re- process it as raw material for making solid soap. This study was conducted from June 13, 2012 to July 20, 2012 at SME Panji Jaya, Segoroyoso, Pleret, Bantul, Yogyakarta and the material was tested in the Chemical Laboratory of Leather Technology Academy, Yogyakarta. The samples are waste cooking oil after used for frying krecek (buffalo skin cracker) for 2-3 times. Utilization of waste cooking oil was done with the purification process consisting of three phases; the removal of seasoning (despicing) in which then the waste cooking oil was filtered with filter paper, and then neutralized with 15% NaOH and bleached using activated carbon as much as 10% of the waste cooking oil used. The purified waste cooking oil was used as raw material for making solid soaps. Cooking oil that has been purified again decreased its FFA levels so that its quality improved. The test result of solid soap compared with SNI 06-3532-1994 shows that it has moisture content of 17.9%, the amount of free fatty acids 61.16%, alkali-free 0.52%, free fatty acids 0.74, lathering number 200, negative mineral oil 80, and pH = 6.